Thermal and Mechanical Properties of Walnut Shell and Glass Fiber Reinforced Thermoset Polyester Composites - Onat, Ayhan; Serdar Pazarlioglu, S.; Sancak, Erhan; Ersoy, Sezgin; Beyit, Ali; Erdem, Ramazan (Asian Journal of Chemistry, 2012)
Recent studies have shown that focusing on industrial waste materials will enable us to recover the economical values. In line with the objective of present study, walnut shell is a waste material was selected to ensure economic recovery. Furthermore, biaxial fiber glass based fabrics were used in order to improve the mechanical properties of the composite materials to be produced. Thermosetting polyester resin was used as matrix material in producing composite materials. Nine different composite materials were produced as a result of addition of walnut shells at different sizes and ratios. Mechanical tests and thermal conductivity tests of these composite materials were carried out and the results were assessed.